A random walk to success - Nicholas, Hastie (My University, 2017)
I have been so privileged and fortunate to have had such a long, enjoyable and fulfilling career in science. I will start the talk by reminiscing about my slow start with a rather mediocre performance in high school. I will then go through the various stages of my career, from undergraduate through to PhD student to postdoc, group leader to eventual Institute Director . There will be some science, quite a few (I hope) humorous anecdotes and a reflection on the rather non-planned path that took me to where I am today . Most important is to acknowledge all the wonderful colleagues and lab members over the years who have been responsible for any success I have had.
Keywords: Genética; Wt1; Molecular biology; Genetics